An international study of correlates of women’s positive body image - Torres, S.; Araújo, C. A.; Fitzgerald, A.; Dooley, B.; Leondari, A.; Costa, C. M.; Olenik-Shemesh, D.; Sygkollitou, E.; Burusic, J; Boone, L.; Šuvak-Martinović, M.; Välimäki, M.; et al. (European Journal of Investigation in Health, Psychology and Education, 2022)
Positive body image (PBI) has received attention in the recent research literature. Despite this, its role in daily functioning in different cultural contexts, particularly its potential relationship with academic outcomes, is still lacking. This study aimed to offer an international perspective on the association between PBI and body mass index (BMI), perceived academic achievement, and educational aspirations, as well as the mediating role of self-esteem. A cross-national study was conducted in eight European countries with a total of 2653 female university students. Participants completed an online survey measuring PBI (conceptualized as body appreciation), self-esteem, perceived academic achievement and aspirations, and body mass index (BMI). Results revealed differences in PBI between countries (low magnitude). PBI correlated negatively with BMI in all national groups (low-to-moderate magnitude). Mediation analysis showed that self-esteem mediated the association between PBI and academic variables. Findings from this study suggest that building students’ self-esteem and PBI can be a suitable way to boost academic success.